2007
DOI: 10.1002/j.2168-9830.2007.tb00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Our Students: A Longitudinal‐Study of Success and Failure in Engineering With Implications for Increased Retention

Abstract: In spite of considerable research about the poor retention rate of undergraduate engineering students, we still have an inadequate understanding of the factors that affect students' decisions to remain in engineering programs and their ability to perform well enough to be retained. Although continued study is needed of external factors such as curricular requirements, admissions criteria, and test scores, we also need to know much more about the relationships between curricular experiences and students' learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(132 citation statements)
references
References 22 publications
4
121
0
Order By: Relevance
“…The study by Freire (1972) also suggested that the traditional model of instruction, utilising lectures and other chalk and talk methods to passive students, is not only ineffective but also disadvantages some student groups whose learning styles and approach to problems are highly valued in the engineering profession. The research by Bernold et al (2007) is in general agreement with this fi nding, stating that those with learning styles that deviate from traditional teaching methods tend to leave the more traditionally taught lecture environment. Providing fi rst-year engineering students with an active learning environment, in addition to faculty mentoring and discipline-specific advice, has been demonstrated to have a positive effect on the retention rates of female engineering students and other minority groups (Hoit & Ohland, 1998;Webster & Dee, 1998).…”
Section: Action Learning In the Context Of Higher Educationsupporting
confidence: 74%
“…The study by Freire (1972) also suggested that the traditional model of instruction, utilising lectures and other chalk and talk methods to passive students, is not only ineffective but also disadvantages some student groups whose learning styles and approach to problems are highly valued in the engineering profession. The research by Bernold et al (2007) is in general agreement with this fi nding, stating that those with learning styles that deviate from traditional teaching methods tend to leave the more traditionally taught lecture environment. Providing fi rst-year engineering students with an active learning environment, in addition to faculty mentoring and discipline-specific advice, has been demonstrated to have a positive effect on the retention rates of female engineering students and other minority groups (Hoit & Ohland, 1998;Webster & Dee, 1998).…”
Section: Action Learning In the Context Of Higher Educationsupporting
confidence: 74%
“…4 Furthermore, scholars have revealed that women and historically underrepresented racial/ethnic minorities (URMs) -Blacks, Hispanics, and Native Americans -face unique barriers (e.g., academic, social) to their success and ultimate degree completion in college, especially in science and engineering disciplines. [13][14][15][16][17][18][19][20] When comparing students' use and engagement with educational technology, differences also exist across gender. Researchers have shown that females report lower confidence, later adoption, less frequent use of educational technology such as multimedia, lower use for academic purposes, and interaction with less advanced forms of educational technology than males.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lack of student engagement in classrooms has been one of the serious concerns that cut across most of the engineering schools. This critical concern, often neglected in classrooms, results in serious attention problems among students, leading to their incompetence and poor retention rates 1 . This issue is more relevant in HBCUs (Historically Black College or University) where the retention rates were reported less than 50% 2 .…”
Section: Introductionmentioning
confidence: 99%